Weight Loss Innovation with Direct and Practical Measurable Targets - P, F. Dwi Basuki; Yunita, Yunita; Atmaja, Elsa Mukti (Akademi Keperawatan RSPAD Gatot Soebroto, 2023)
Nutritional status is one of the factors that plays a role in achieving the quality of healthy, intelligent, productive and independent human resource performance. Factors that influence nutritional status include nutrient intake and physical activity. Guidelines for daily food consumption and the implementation of healthy behavior in Indonesia are in the form of the General Guidelines for Balanced Nutrition (PUGS) and abroad, one of which is the Traffic Light Diet. The Traffic Light diet concept in Australia is used for labeling the nutritional content of packaging at high (red), yellow (medium), green (low) levels. In an effort to improve Healthcare Workers Wellbeing, an innovation was designed that can facilitate the implementation of the selection of types of food and the implementation of physical activity according to PUGS. The purpose of this study is to achieve optimal weight loss and changes in exercise frequency. This study uses a Quasy Experimental design (pre and post test) with variables of body weight (BW), Body Mass Index (BMI), and physical activity. Initial data collection for BW and BMI from October 2022 to December 2022. Implementation of the innovation from February to March 2023. Data were analyzed using SPSS 22 with paired t-test, Wilcoxon and chi square tests. The results of this study were to select 10 Nutritionists with overweight nutritional status to implement the innovation for 8 weeks. The results of the statistical test showed a significant decrease in BB and BMI after the innovation (p 0.000 and 0.005). The results of the statistical analysis with chi square showed that the frequency of exercise was related to weight loss (p 0.033). The conclusion drawn is that innovation helps maintain diet and physical activity so that it is more effective in losing weight. Innovation can be used as a reference source to improve Healthcare Workers Wellbeing in a wider environment.